Integrating BIM with positioning system to develop a precast installation system - Zhou, Yitian (2016)
Building Information Modelling (BIM) has been adopted widely by project managers for project information management and its sharing among different stakeholders. However, in actual construction process, a building information model is detached from the physical construction processes. Current practices involve manually inputting information into a building information model to show changes and progresses in the construction process, and this method is time-consuming, inefficient and error-prone. The Building and Construction Authority (BCA) has been paying more attention on assisting small and medium enterprises to improve construction productivity by encouraging the facilitation of precast elements in a modern way. In order to address this issue, this research paper will propose a precast installation system, which makes use of positioning systems to track the position of the precast element during installation. The feasibility of different types of positioning systems are analysed in this paper, and the Global Positioning System (GPS) and the Local Positioning Systems (LPS) are selected due to their ubiquity, low-cost and high accuracy. The location information is logged, extracted and integrated into the building information model in real-time. By doing so, the building information model will be synchronised with the actual construction process, making transfer of information easier and more efficient. Moreover, tower crane operators can also make use of the real-time tracking information to assist in visualising the installation process.